Treatment outcomes of patients with acute promyelocytic leukaemia between 2000 and 2017, a retrospective, single centre experience. (June 2020) - Chien, Nicole; Varghese, Chris; Green, Taryn N.; Chan, George; Theakston, Edward; Eaddy, Nicola; Doocey, Richard; Berkahn, Leanne; Hawkins, Timothy; Browett, Peter J.; Kalev-Zylinska, Maggie L.
Highlights: We report 70 APL patients, 47 received ATRA-chemotherapy, 23 received ATO. Our diagnostic strategy incorporating PML immunofluorescence test resulted in median time to ATRA initiation of 11.2 h. Bleeding patients were started on ATRA sooner. Fast ATRA initiation improved early but not late outcomes. ATO reduced coagulopathy, transfusion requirements and disease-related deaths. Abstract: All-trans retinoic acid (ATRA) and arsenic trioxide (ATO) are effective induction therapy for acute promyelocytic leukaemia (APL). However, early thrombo-haemorrhagic complications and mortality remain high. We aimed to investigate how the timing of ATRA initiation and the inclusion of ATO influence patient outcomes. Clinical records were retrospectively reviewed for all patients treated for APL in a single, tertiary centre during 2000−2017. Among 70 patients with APL, 36 (51.4%) presented with thrombo-haemorrhagic complications, and four (5.8%) died within 30 days. The median time to ATRA initiation was 11.2 (range 0–104) h from the time of admission. Patients requiring more transfusions started on ATRA sooner ( P = 0.04). Patients with adverse early events did not start ATRA later ( P = 0.99). Nevertheless, patients that required additional tests for diagnosis (PML immunofluorescence or molecular) started on ATRA later (28.5 versus 5.3 h; P < 0.0001), and had more thrombo-haemorrhagic complications ( P = 0.04). Long-term survival was actually better in patients who started ATRA later ( P = 0.03), which is likely explained by higher proportion of low risk patients in this group. Patients treated with ATO (n = 23) maintained higher fibrinogen levels and required less transfusions during induction ( P < 0.05), with no disease-related deaths in this group over a median follow-up time of 37.8 months (interquartile range 44.9 months). In summary, fast ATRA initiation reduces early but not late adverse events in APL patients, and the inclusion of ATO helps further improve both early and late outcomes in APL.